Toward a Comprehensive Model of Organizational Evolution: Dynamic Capabilities for Innovation and Adaptation of the Enterprise Model. (August 2016) - Zollo, Maurizio; Bettinazzi, Emanuele L.M.; Neumann, Kerstin; Snoeren, Peter
Abstract : Plain language summary: This article argues that the rapid evolution of expectations and influence capacity by corporate stakeholders requires managers in MNCs not only to adapt operating activities, but to rethink the purpose and overarching goal of the business enterprise, adapting it from a shareholder‐primacy to a multi‐stakeholder enterprise model. This complex adaptation process, however, requires the development of a specific form of competence to be developed and honed, different in kind from the typical capabilities focused on organizational change. With the help of concrete examples of sustainability‐driven change initiatives, we discuss how the two enterprise models differ and how the development of this new type of competence facilitates the transition from one to the other. Technical summary: This article argues that the dynamic capabilities framework can be useful to study the evolutionary change processes that MNCs go through as they strive to innovate and adapt to societal pressures related to corporate sustainability. These pressures require MNCs to rethink and adapt core organizational elements and we argue that current dynamic capabilities theory is not sufficiently developed to explain these adaptive efforts. We suggest refining and extending theory in two directions: (1) distinguishing between behavioral, cognitive, and relational organizational elements as objects of the innovation, change, and learning dynamics; and (2) distinguishing between capabilities specific to generative variation and selection of innovative change and adaptation ideas from those specific to their diffusion and retention. Copyright © 2016 Strategic Management Society